Increased cardiovascular risk markers in obesity are associated with body adiposity: Role of leptin - Gómez-Ambrosi, Javier; Salvador, Javier; Silva, Camilo; Pastor, Carlos; Rotellar, Fernando; Gil, María J.; Cienfuegos, Javier A.; Frühbeck, Gema (Thrombosis and Haemostasis, 2006)
Epidemiological studies have shown that obesity is associated with increased blood concentrations of proinflammatory factors and markers of endothelial dysfunction such as fibrinogen, C-reactive protein (CRP), and von Willebrand factor (vWF). We analyzed the association of these markers with percentage of body fat (BF), and the influence of leptin in a cross-sectional study of 1,089 subjects (366 men) aged 44 (34–53) [median (interquartile range)] years, who were classified as obese or non-obese according to BF estimated by whole-body air displacement plethysmography. Obesity was defined as BF ≥ 25% in men and ≥ 35% in women. Compared with non-obese subjects (mean ± SD), obese patients had higher concentrations of fibrinogen (312± 78 vs. 342 ± 81 mg/dl, P < 0.001), CRP (0.41 ± 0.75 vs. 0.75± 1. 04 mg/l, P = 0.014), vWF (107 ± 29 vs. 123 ± 55%, P < 0.001), and leptin (10.4 ± 6.5 vs. 37.5 ± 26. 1 ng/ml, P < 0.0001). A positive correlation was observed between BF and fibrinogen (r = 0.266; P < 0.0001), logCRP (r = 0.409; P < 0.0001), and vWF (r = 206; P < 0.0001). Leptin was correlated with fibrinogen (r = 0.219, P < 0.0001), logCRP (r = 0.339, P < 0.0001), and vWF (r = 0.124, P = 0.002), but the statistical significance was lost after including BF in adjusted-correlation and multivariate analysis, suggesting that they are not regulated by leptin per se. In conclusion, the obesity-associated increase in the circulating concentrations of fibrinogen, CRP, and vWF is highly associated to BF and apparently not determined by leptin.
Keywords: Obesity; adipose tissue; inflammation; leptin; insulin resistance